COMPELLING NEED FOR DHHS GENERAL ADMINISTRATION MANUAL CHAPTER 1-60 POLICY TO ESTABLISH A SMOKE FREE ENVIRONMENT IN HHS BUILDINGS - OASH; OM; TUCKER E (Tufts Archival Research Center, 2007)
Marginalia; Report presenting the case that the U.S. Public Health Service should not have to negotiate smoking regulations with labor unions. Includes Congress' definition of "compelling need," and a history of "compelling need" case studies.